Perempuan Pedesaan Merespon Krisis Iklim: Kajian Ekofeminisme Terhadap Perempuan Di Sungai Batanghari: AN ECOFEMINISM STUDY ON WOMEN IN BATANGHARI RIVER - Angraini, Peppy; Ramona, Elza; Amin, Al (Jurnal Masyarakat dan Budaya, 2023)
Women in the Batanghari watershed experienced changes and lost their livelihoods due to conversion of plantation. Women worked in rubber plantations and agriculture and had to stop working altogether, or worked in plantation companies as daily laborers. Land conversion did not only change the pattern of livelihoods, but also changed the way of life of women. Some women even encouraged their husbands and sons to mine gold in the river to provide for the family. This research was conducted in two villages; Teluk Kuali and Melako Intan were opposite and separated by the Batanghari River. This research aimed to answer the question whether women in the two villages had knowledge about the climate crisis, and how rural women respond to the ongoing climate crisis. In collecting data, this research used interview techniques and direct observation. Ecofeminism is used to analyze this research.